2020
DOI: 10.1075/jicb.17028.alf
|View full text |Cite
|
Sign up to set email alerts
|

Effects of focus on form on primary CLIL students’ foreign language performance in task-based oral interaction

Abstract: In content and language integrated learning (CLIL) programmes, attention to language can be easily overlooked behind the assumption that language learning will take place incidentally. This study aimed at analysing the effects of a balanced integration of content and language on fifth graders’ foreign language (FL) oral performance. Two groups of participants had been doing CLIL in the form of an Information and Communication Technology (ICT) subject … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
1
2
0
1
Order By: Relevance
“…FonF was found to enable learners to obtain sufficient meaning negotiation and form negotiation, which is helpful for constructing the connection between the linguistic meaning and form. This observation is consistent with previous studies that a teaching approach with rich interaction and meaning-focused activities is beneficial to fluency (Sato and Lyster, 2012;Arslanyilmaz, 2013;Pena and Pladevall-Ballester, 2020;Hyun, 2021).…”
Section: The Influence Of Fonfs and Fonf On L2 Chinese Oral Productionsupporting
confidence: 93%
See 1 more Smart Citation
“…FonF was found to enable learners to obtain sufficient meaning negotiation and form negotiation, which is helpful for constructing the connection between the linguistic meaning and form. This observation is consistent with previous studies that a teaching approach with rich interaction and meaning-focused activities is beneficial to fluency (Sato and Lyster, 2012;Arslanyilmaz, 2013;Pena and Pladevall-Ballester, 2020;Hyun, 2021).…”
Section: The Influence Of Fonfs and Fonf On L2 Chinese Oral Productionsupporting
confidence: 93%
“…Most studies have found that FFI has a positive impact on L2 oral acquisition (Snellings et al, 2002;Toni and Hassaskhah, 2018). Research on children's L2 acquisition has shown that FFI is beneficial to improve fluency (Pena and Pladevall-Ballester, 2020) and accuracy (Hyun, 2021). Compared with non-FFI instruction, FFI was more beneficial for college students' L2 oral grammar, vocabulary, and fluency (Lee, 2016).…”
Section: The Influence Of Form-focused Instruction On L2 Oral Acquisi...mentioning
confidence: 99%
“…Es más, son numerosos los estudios en los que se hace referencia a la necesidad de una formación específica de la enseñanza en otro idioma en cualquier asignatura (p. ej. Alfonso & Pladevall-Ballester, 2020;Barrios & Milla-Lara, 2020;Codó, 2020;Custodio & García, 2019;Hernando et al, 2017;Pérez-Cañado, 2015, 2017 Mdn= Mediana; TRS = tiempo real de la sesión; TCM = tiempo de compromiso motor; TO = tiempo de organización; TT = tiempo empleado en la tarea. 2022, 40(1) cretamente en la asignatura de EF, una materia especial dentro del currículo, la única eminentemente práctica y cuya esencia es el movimiento.…”
Section: Discusión Y Conclusionesunclassified
“…However, there is currently a lack of pedagogical guidelines for the development of this bilingual approach in general, and in PE in particular (García-Calvo & Nieto, 2022), as well as a lack of research on the results obtained from the implementation of these educational approaches (Chiva-Bartoll et al, 2015;Martínez-Hita et al, 2022). Along the same lines, the lack of appropriate teacher training is another of the needs raised by the scientific community (Barrios & Milla-Lara, 2020;Codó, 2020;Custodio & García, 2019;Pena & Pladevall-Ballester, 2020;Pérez-Cañado, 2015), such training being necessary to achieve the expected results of quality bilingual education. Thus, Nieto (2019) highlights that despite the high degree of student satisfaction with CLIL bilingual programmes, there are practical shortcomings in their implementation.…”
Section: Introductionmentioning
confidence: 99%